Controls on Palaeogene deep-sea diatom-bearing sediment deposition and comparison with shallow marine environments - C. Figus; C. Figus; J. Renaudie; O. M. Bialik; O. M. Bialik; J. Witkowski (Biogeosciences, 2025)
Diatoms are the key players in the present-day global biogeochemical cycles. Yet, the diatom flux response to the dynamically changing climates of the Palaeogene has long been subject to divergent interpretations. We present a synthesis of Palaeogene deep-sea diatom-bearing sediment occurrences in time and space in order to gain new insight into inter-basin and latitudinal distribution of diatom accumulation zones from the Cretaceous–Palaeogene boundary to the Oligocene–Miocene transition. Our dataset includes 189 sites drilled in the Atlantic, Pacific, and Indian oceans and in the Arctic. It suggests that the number and distribution of deep-sea diatom-bearing sediment occurrences are mainly controlled by the nutrient availability and ocean circulation. Climate appears to have only an indirect correlation with our results, which may be linked to the expansion of the Antarctic Ice Sheet during the Oligocene global cooling. A comparison of our results with the temporal distribution of shallow marine diatomite occurrences (Figus et al., 2024a) suggests that the increase in the number of deep-sea diatom-bearing sediment occurrences (particularly in the Atlantic) during the diatomite gap (∼ 46 to ∼ 44 Ma) in shallow marine settings is indirectly related to the tectonic reorganizations occurring during this period: palaeogeographic changes caused the cessation of shallow marine diatomite deposition and increased nutrient availability in the oceans through continental weathering intensification. We also challenge the previous views on geographic shifts in the key loci of biogenic silica accumulation, which generally indicate that as global cooling progressed through middle and late Eocene, the Southern Ocean was gradually becoming the key biogenic silica sink. Our synthesis shows – albeit in a non-quantitative perspective – that through most of the Palaeogene, low to mid-latitude areas, especially in the Atlantic Ocean, were the locus of widespread biogenic silica deposition and burial.